“I’m changing the story here": Emotional schema formation and communication between caregivers and children - Schmechel, Lindey Kaye (My University, 2025)
Emotions are a universal human experience; however, much work remains to be done in terms of understanding the formation of emotions and beliefs related to them, and how one’s culture and/or identity may impact them. While research has been conducted regarding emotional regulation and emotional reactions, a deeper exploration into the processes regarding our core beliefs about emotions (i.e., emotional schemas) is necessary to bridge a gap in the existing literature. If caregivers are to make intentional choices about the messages they send children regarding emotions and emotional beliefs, something that has been found to have long- lasting impacts, it is important for researchers and those aiming to help them to better understand the process of creating emotional schema. In order to help caregivers create more effective and positive socialization experiences with their own children, it is imperative to first aid caregivers in distinguishing what they believe about emotions and why. To this end, this study used a qualitative narrative approach to (a) highlight commonly experienced socialization milestones around emotions across childhood, adolescence, and new parenthood and (b) provide recommendations for caregivers and professionals in helping fields (e.g., therapists, educators) based on these experiences. Guided by symbolic interactionism theory (Stryker, 2008) and utilizing a feminist framework (Biana, 2020), I conducted nine interviews with six caregivers of preschool-aged (3-5 years) children around the messages they received as children regarding emotions, how these shifted over time, and what meanings around emotions they would want their own children to have. Using thematic analysis to interpret these interviews (Braun & Clarke, 2022), the coding team identified five themes related to participants’ meaning-making around emotions: (a) Culture/Context, (b) Changes Over Time, (c) Intentionality, (d) Parenting as a Practice, and (e) Emotion-Specific. The findings of the interviews emphasize the important role that caregivers tend to play in their children's lives when it comes to the formation of emotional schema but also highlight how inherently embedded in our current culture these messages can be. Acknowledging the influence of both caregivers and societal norms on the formation of emotional schema is an important step in working to determine what fits for the child or not, to help parents more effectively communicate messages regarding emotions with their children, and to disrupt intergenerational patterns that have been repeated and caused harm for far too long.
Emotional schema formation and communication between caregivers and children
Keywords: Emotional schema; Socialization of emotions; Intersectionality; Socialization experiences; Intersectionality